One pot synthesis of Biginelli 3,4-dihydro-1H-pyrimidin-2-ones and 1,2,3,4-tetrahydro pyrimidines (Bangladesh Journal of Scientific and Industrial Research, 2020)
A simple and practical route for the Biginelli cyclocondensation reaction using anhydrous ZnCl2 as a catalyst in n-heptane-toluene medium by reaction of substituted benzaldehydes,1a-d (1a=2-ClC6H4-, 1b=2-BrC6H4- and 1c=4-ClC6H4-,1d=2-H3CC6H4-) with 1, 3-dicarbonyl compounds, 2a-b (2a= ethyl acetoacetate and 2b= acetylacetone) and urea or thiourea, 3a-b to give the corresponding Biginelli 3,4-dihydro- 1H-pyrimidin-2-ones and 1,2,3,4-tetrahydro pyrimidines, 4a-d. The structures of the compounds 4a-d were confirmed by their ultraviolet, infrared, 1H NMR, 13C NMR spectra and elemental analyses.Bangladesh J. Sci. Ind. Res.55(3), 173-180, 2020